Chiquitita - Oldfield, Jenny (Hodder Children's London, 2001)
Chiquitita is a young mare taken from the wild herd to be tamed and worked without force. The method demands great patience from Wayne Raburn but his ranch hand, Walter, secretly uses harsher methods which soon ruin his boss's good work